ANALYSIS OF AMINA WADUD’S HERMENEUTIC WEAKNESSES THROUGH WASATIYYAH YUSUF QARDHAWI’S PERSPECTIVE
ABSTRACT The emergence of some activists from the feminist movement who consider the need for deconstruction and reconstruction as well as interpretation of the Al-Qur’an. This case is aimed at achieving a fairer meaning, and no party is marginalized. Amina Wadud is one of the feminist figures who is active and active in this field. Various issues of injustice contained in the Al-Qur’an are explained again according to his point of view. However, the spirit of interpretation with a hermeneutical style of gender equality needs to be analyzed from a wasat